A importância dos testes de software: o que testar, como testar e o porquê testar - OLIVEIRA, Edson Rodrigo de (2024)
This article addresses the importance of software testing, exploring what should be tested, how to conduct tests, and why they are essential in the software development process. The main aspects to be considered when testing software, different testing approaches and techniques, as well as the benefits that testing brings to software quality and reliability, will be discussed.